Uncommon valor : the recon company that earned five Medals of Honor and included America's most decorated Green Beret - Moore, Stephen L. (Naval Institute Press, 2018)
"Uncommon Valor is about the formation and operation of an advanced Special Forces recon company during the Vietnam War. Code-named the Studies and Observations Group, SOG was the most covert U.S. military unit in its time and contained only volunteers from such elite units as the Army Green Berets, Navy SEALs, and USAF Air Commandos. SOG warriors operated in small teams, going behind enemy lines in Laos and Cambodia and along the Ho Chi Minh Trail, tasked with performing special reconnaissance, sabotaging NVA ammunition, attempting to rescue downed U.S. pilots, and other black ops missions"--